SAT-180 Adrenocortical Carcinoma - A Tertiary Center’s Recent 5-Year Experience - Ehrenwald, Michal (J Endocr Soc, 2020)
BACKGROUND: Adrenocortical carcinoma (ACC) is a rare endocrine malignancy with poor prognosis. The aim of this study was to characterize patients diagnosed with ACC at a single center between 2014-2019. METHODS: We retrospectively reviewed data regarding demographics, tumor characteristics and functionality, treatment and survival. RESULTS: The study cohort included 27 subjects (56% females), followed for 27±10.6 months. The mean age at diagnosis was 49.4±9 years. Co-morbidities at presentation included hypertension (63%), diabetes mellitus (22%) and dyslipidemia (26%). 74.1% of tumors were functioning – of which 85% were cortisol-secreting and 15% androgen-secreting. Aldosterone was secreted additionally in 15%. ENSAT stage at diagnosis was stage 1 in 15%, stage 2 in 35%, stage 3 in 12% and stage 4 in 38%. Eighty-nine % of patients underwent surgery. Treatment with mitotane was initiated in 82% of patients, reaching a mean maximal dose of 3.3 ±0.4 grams/day. Chemotherapy and/or radiation were given in 37% and 22%, respectively. Several patients (14.8%) had a second primary cancer, diagnosed before ACC in 75%. Progression was observed in 48% of patients, with a progression-free survival of 8.3±6.6 months. Thirty-five % of patients died during follow up, time to death was 12.8±0.4 months. Twenty two % of patients survived over 30 months after diagnosis. KI67 above 20% or stage above 2 negatively affected survival. CONCLUSIONS: ACC remains a rare disease with a poor prognosis. However, it is a heterogeneous disease, with some patients achieving survival of over 30 months after diagnosis. Further characterization of this population may improve our understanding of the biology and treatment of this rare disease.